2020
DOI: 10.1021/acsami.0c00652
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Targeting Gene Vector for Visual Tracking of Bcl-2 siRNA Transfection and Anti-Tumor Therapy

Abstract: Tumor targeting provided more effective gene therapy. Bcl-2 is an oncogene, and Bcl-2 small interfering RNA (Bcl-2 siRNA) can inhibit its expression. Here, a fluorescent and gene-loading capacity vector DPL, derived from diketopyrrolopyrrole (DPP), was developed for Bcl-2 siRNA-targeted delivery and tumor imaging in vitro and in vivo. The vector DPL showed a significant emission enhancement after interacting with siRNA, which was used to track the gene transfer process. Compared to commercial transfection reag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…6S is a fat-soluble drug, and its nonaqueous solvent dosage form (polyoxyethylene ether castor oil) results in its large toxic and side effects and low bioavailability. Encapsulation of 6S into nanobubbles increased its permeability and accumulation in tumors, which is due to the effective internalization of drug-loaded nanobubbles by the cell uptake endocytosis mechanism, thereby enhancing EPR effects. Our study showed that intraperitoneal injection of paclitaxel caused acute liver damage in nude mice, which might be related to the first-pass effect through the portal vein to the systemic tissue, and the combined use of PTX and free 6S further aggravates liver damage. At present, PTX is usually administered intravenously to avoid the first-pass effect of the liver, thereby reducing the effect of the drug on the liver.…”
Section: Resultsmentioning
confidence: 73%
“…6S is a fat-soluble drug, and its nonaqueous solvent dosage form (polyoxyethylene ether castor oil) results in its large toxic and side effects and low bioavailability. Encapsulation of 6S into nanobubbles increased its permeability and accumulation in tumors, which is due to the effective internalization of drug-loaded nanobubbles by the cell uptake endocytosis mechanism, thereby enhancing EPR effects. Our study showed that intraperitoneal injection of paclitaxel caused acute liver damage in nude mice, which might be related to the first-pass effect through the portal vein to the systemic tissue, and the combined use of PTX and free 6S further aggravates liver damage. At present, PTX is usually administered intravenously to avoid the first-pass effect of the liver, thereby reducing the effect of the drug on the liver.…”
Section: Resultsmentioning
confidence: 73%
“…Specific targeting of BCL-2 by siRNA in various malignancies including breast cancer demonstrated growth inhibition, apoptosis induction, and enhanced susceptibility to chemotherapy in vitro and preliminary in vivo studies [ 12 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ]. So far, clinical application of siRNA-based therapies is hampered by unspecific effects such as complement activation and induction of cytokine release.…”
Section: Discussionmentioning
confidence: 99%
“…Clearly, the fluorescence intensity at the tumor site was stronger than that at other major organs, and except for the liver, other organs displayed no or very weak fluorescence intensity, indicating that the liver was the main metabolic pathway of TTC-L-M-4/DOPE/pGL-3. 24,51 To assess the in vivo cooperative anti-cancer efficacy, lipoplexes were subcutaneously injected into HeLa orthotopic tumor-bearing mice, followed by irradiation (LED light, 450 nm, 10 mW cm À2 ) on the tumors for 30 min at 24 hours post-injection (Fig. 6(A)).…”
Section: In Vivo Antitumor Efficacymentioning
confidence: 99%